Nanostructured Titan - a New Material for Dental Implants - J. Petruželka; L. Dluhoš; D. Hrušák; J. Sochová (Czech Dental Chamber, 2006)
New materials have been developed for dental substitutions, in order to better suit to the demands made from the medical point of view. A prospect material for such purposes is the nanostructured titan (nTi). The paper compares its qualities with those of other materials being used for the same purpose. nTi is, in the same way as the commercially pure titan (cpTi), inert, does not contain any, even only potentially toxic or allergenic ingredients and its specific stability is higher than in any other kinds of materials used for dental implants. nTi has been used to produce screw implants Nanoimplant® of the 2.4mm diameter and the length of intraossal part 12 mm. Immediately after the introduction of three nanoimplants into the frontal part of low jaw of the patient these were treated with a temporary fixation bridgework. The course of healing even in the early postoperative period was without any complications. This is the first application of nTi dental implant in the world.